(untitled) (Faridpur Medical College Journal, 2019)
Sertoli-Leydig Cell Tumor (SLCT) is an extremely rare and distinctive sex cord-stromal tumor. Ovarian sex cordstromal tumors are infrequent tumors that differ from the more frequent epithelial neoplasm and have strong association with hormone-mediated syndromes, presentation in a wide age range, and the diagnosis is usually at early-stage disease with a good outcome. SLCT typically present with pelvic or abdominal pain and tenderness, mass, and or abnormal menstruation, and with hormonal activity reported predominantly after menarche. We report a case of 18-year-old unmarried female presented with severe pain and lump in the lower abdomen and also a case of primary amenorrhea with normal secondary sex characters. She was a suspected case of twisted ovarian tumor on USG and underwent laparotomy followed by total excision of the lump and histopathology report revealed Sertoli- Leydig Cell Tumor. Though it is a rare tumor, the possibility of Sertoli-Leydig Cell Tumor in a young woman should be kept in mind. Faridpur Med. Coll. J. Jul 2018;13(2): 104-107